Correlation of the Get-Up-And-Go Test With The Tinetti Test when assessing the risk for falls in elderly persons - Gálvez Cano, Miguel (2010)
Objective: To find a correlation between the Get-Up-And-Go Test and the Tinetti test. Material and Method: This is a study that assessed the concordance of the aforementioned tools. The population consisted in elderly persons attending the geriatrics outpatient clinic in Hospital Nacional Cayetano Heredia. The sample was taken using the accidental sampling method, and the first 100 patients attending the geriatrics outpatient clinic during March 2005 were included.  Results: Mean age of patients was 75.2 ± 7.46 years, 31% declared they had one or more falls during the last year. The measured correlation between the two tests using Kappa statistics was 0.81 with p<0.001, for a cutoff point for the Get-Up-And-Go test set in 20 seconds. Conclusions: The is a correlation between a complex method, the Tinetti test, and a simple and short method, the Get-Up-And-Go test, which may be used as an initial tool when assessing the risk for falls.